(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2022)
Pleurotus ostreatus is an edible fungus that is produced on a wide variety of agricultural and agroindustrial wastes, due to its great capacity to colonize and degrade lignocellulosic substrates. The objective of this work was to evaluate the kinetics of radial growth, to obtain mycelium and the production of Pleurotus ostreatus in fresh state, using for its growth tender corn cob husk, legume husk (pea, bean and broad bean). In the first phase, mycelial growth was determined and in the second phase, production of the fungus Pleurotus ostreatus. For radial growth or mycelial growth, a completely randomized experimental design was used, with five treatments and five replicates. In the kinetics of radial growth, which was the obtaining of mycelium, the one that showed the best behavior in the growth of Pleurotus ostreatus was the culture medium Papa dextrose agar plus the inclusion of pea husk (Pisum sativum) 74 mm at 168 hours of growth, while the best harvest yield of Pleurotus ostreatus was fava bean husk (Vicia faba) 151.40 g of Pleurotus ostreatus, per kilogram of substrate in the first harvest. With these results, there is an alternative to use vegetable waste generated in the central market of the canton of Quevedo, Province of Los Ríos, Ecuador, to obtain a foodstuff and reduce the contamination that waste generates in the environment.